2023
DOI: 10.1177/17474930231182018
|View full text |Cite
|
Sign up to set email alerts
|

Occult contrast retention post-thrombectomy on 24-h follow-up dual-energy CT: Associations and impact on imaging analysis

Abstract: Background Following reperfusion treatment in ischemic stroke, CT imaging at 24-hours is widely used to assess radiological outcomes. Even without visible hyperattenuation, occult angiographic contrast may persist in the brain and confound Hounsfield Unit-based imaging metrics such as Net Water Uptake (NWU). Aims We aimed to assess the presence and factors associated with retained contrast post-thrombectomy on 24-hour imaging using Dual Energy CT (DECT), and its impact on the accuracy of NWU as a measure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Importantly, they found that NWU did not correlate with functional outcome at 90 days in the presence of hemorrhagic transformation or thrombectomy. These findings may be partially due to angiographic iodine retention, which may confound NWU measures which is dependent on Hounsfield-unit of the infarct tissue ( 32 ). Iodine extravasation may account for 27–84 percent of hyperdense lesions on CT post-thrombectomy at 24-h ( 53 , 54 ).…”
Section: Tissue-based Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, they found that NWU did not correlate with functional outcome at 90 days in the presence of hemorrhagic transformation or thrombectomy. These findings may be partially due to angiographic iodine retention, which may confound NWU measures which is dependent on Hounsfield-unit of the infarct tissue ( 32 ). Iodine extravasation may account for 27–84 percent of hyperdense lesions on CT post-thrombectomy at 24-h ( 53 , 54 ).…”
Section: Tissue-based Propertiesmentioning
confidence: 99%
“…While no statistically significant difference were demonstrated in this small and likely underpowered cohort, notably 2 of 10 patients demonstrating more than 20% differences in NWU values between conventional CT and DECT, implying that the effect of iodine may affect NWU measures in a substantial proportion of patients. A subsequent larger multicenter study ( n = 125) aimed to provide a more definitive analysis of the confounding effects of post-thrombectomy iodine on follow-up CT demonstrated that contrast-adjusted NWU values were significantly higher than non-adjusted values, and correlated with measures of cerebral oedema, such as midline shift and rHV ( 32 ). They demonstrated that even without visible hyperdense lesions on follow up imaging at 24 h, angiographic iodine contrast is retained in brain parenchyma.…”
Section: Tissue-based Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genuine inaccuracies in mismatch estimates exist but are often exaggerated by inaccuracies in assessment of the follow-up infarct volume reference standard due to early temporary diffusion lesion reversal 11 or the insensitivity of noncontrast computed tomography assessments that can be obscured by residual contrast staining. 15 How frequently these factors mean that patients assessed as having no mismatch do, in fact, have a clinically meaningful volume of salvageable penumbra and capacity to benefit from reperfusion is uncertain. The SELECT2 16 randomized trial (A Randomized Controlled Trial to Optimize Patient’s Selection for Endovascular Treatment in Acute Ischemic Stroke) found there was no statistically significant heterogeneity in EVT benefit between patients with and without mismatch, and the point estimates favored EVT, regardless of mismatch status, although very few patients had no mismatch using the mismatch ratio <1.2 and absolute mismatch <10 mL definition.…”
mentioning
confidence: 99%